A lady on the edge of ruin - James, Lotte R. (Harlequin historicals., 2023)
A passion that could destroy her reputation but save her heart! Since the traumatic events of her first Season, Lady Mary Spencer's been wary of Society. Tired of feeling angry and bitter, at a seemingly innocuous garden party, she lets her guard down with Luca Guaro. The charming Italian rogue also abhors the ton's dictates and becomes a much-needed light in Mary's life. A liaison with Luca would be scandalous, so why is she so tempted to head to the brink of ruin...?